The effect of feeding different doses of herbal supplements from Hungarian sainfoin on the growth and metabolism in the body of calves - E. V. Sukhanova; N. A. Morozkov; L. V. Sycheva (Аграрная наука Евро-Северо-Востока, 2023)
There have been studied the influence of feeding plant raw material obtained from Hungarian sainfoin having an immunostimulating effect on the growth rate of dairy calves, as well as on morphological and biochemical blood parameters and natural resistance of the animal organism. Calves of the I and II experimental groups in addition to the main diet were fed a phyto supplement made of Hungarian sainfoin mixed with concentrates in doses of 150 and 300 g per head per day during 92 days. The use of herbal supplements in feeding calves ensured an increase in live weight in the animals of experimental groups by 11.0 kg (6.55 %) and by 11.7 kg (6.96 %) (p <0.05) over the period of scientific and economic experiment, compared with analogues of the control group. From the analysis of blood parameters, it should be noted that protein indicators were higher by 1.36 % (I experimental) and by 4.74 % (p < 0.01) (II experimental); there was an increase in hemoglobin at the end of the experiment - by 5.88 % (I experimental) and by 12.15 % (p ≤ 0.01) (II experienced). When determining the indicators of natural resistance, it was found that in calves of experimental groups I and II, the phagocytic activity of leukocytes was higher by 4.16 and 17.29 % (p ≤ 0.01), respectively, in comparison with control animals. Analysis of the data obtained showed that the most optimal dose for use in the diets of heifers is 300 g per head per day, fed to calves of the II experimental group. This is confirmed by the improvement of biochemical, morphological and immunological parameters of animal blood, as well as by higher values of their live weight gain.